Systematic review on right-wing authoritarianism in Peru - Roca, Marcelo Agustin (2024)
Right Wing Authoritarianism is a construct that has been widely studied in Latin America due to the adequate applicability of the scale proposed by Altemeyer. There are several published validations of the construct, and different articles that study its association with other variables. However, there is no systematic review analyzing research regarding the construct and its applicability to a cultural context such as Peru. For this reason, this article aims to review the studies published on Right Wing Authoritarianism in Peru. For this purpose, a search was carried out in the databases of Redalyc, BASE, SciELO, LA Referencia and Google Scholar. The results demonstrate a total of 26 research studies using scales to measure Right Wing Authoritarianism with different variables from 2010 to February 2023. A total of 80.8 % of the studies were carried out within the Peruvian context, 7.7 % included Chile and 11.5 % were cross-cultural studies. A tendency was found to measure the construct in relation to different variables such as Social Dominance Orientation, justification of inequity, right-wing political orientations, ambivalent sexism, intolerance of ambiguity, among others. For this reason, the present systematic review is useful to understand how the relationship between these constructs is manifested in the Peruvian context at present.